ABO and Rh blood groups in patients with Lupus and Rheumatoid Arthritis - Amir Nik; Zahra Mirfeizi; Zahra Rezaieyazdi; Mandana Khodashahi; Shahin Danevash; Mohammad Sobhan Sheikh Andalibi; Mahnaz Abbasi; Maryam Sahebari (Babol University of Medical Sciences, 2021)
Background: Systemic lupus erythematous (SLE) and rheumatoid arthritis (RA) are autoimmune diseases in which the antigen-antibody system plays an important role. As blood group and Rh are determined by the presence or absence of antigens on the surface of red blood cells (RBCs), we aimed to determine the distribution of ABO and Rh blood groups in SLE and RA patients and its association with disease manifestations. Methods: This short communication is based on a study that was conducted on 434 SLE and 828 RA patients. We evaluated the distribution of ABO and Rh blood groups in RA and SLE patients. Results: This study projected that in lupus patients, Coombs-positive autoimmune hemolytic anemia and arthritis were more common among the B blood type and Rh-positive group, respectively. Furthermore, there was no relation between ABO and Rh blood group and rheumatoid factor (RF) and anti-Cyclic Citrullinated Peptide (anti-CCP) seropositivity. Moreover, there was no difference in distribution of blood groups in RA and SLE patients. Conclusion: The higher frequency of blood group B in hemolytic anemia, and positive Rh in arthritis in lupus patients, develop the hypothesis of probable role of ABO blood group antigen in some manifestations of lupus.